A molecular study of the genus Spelaeomyia (Diptera: Phlebotominae) with description of the male of Spelaeomyia moucheti. Issue 1 (December 2016) - Rahola, Nil; Henni, Leila; Obame, Judicael; Ayala, Diego; Makanga, Boris; Lehrter, Véronique; Izri, Arezki; Paupy, Christophe; Depaquit, Jérôme
Abstract Background The genusSpelaeomyia includes four African species considered as being cavernicolous:Spelaeomyia darlingi, Spelaeomyia mirabilis, Spelaeomyia emilii andSpelaeomyia moucheti . Despite a potential role inLeishmania major leishmaniasis transmission in Mali, no molecular studies and only few morphological studies have addressed relationships between species ofSpelaeomyia . Methods Specimens ofSa. moucheti were collected in two different sites in Gabon.Spelaeomyia emilii andSa. darlingi specimens came from Gabon and Mali. Specimens ofSa. mirabilis were collected in the Democratic Republic of Congo and Gabon. All specimens were caught using CDC miniature light traps, then dissected, both heads and genitalia were kept for morphological analysis and the rest of the bodies were kept for molecular processing and analyses. Results Some unidentified males are associated toSa. moucheti females using molecular tools and are described for the first time. A new morphological feature is observed on the spermathecae of the female and new drawings are provided. For the first time a phylogenetic analysis is carried out on rDNA and mtDNA markers and it shows thatSa. moucheti is the sister species ofSa. mirabilis . Conclusions Spelaeomyia moucheti is the sister species ofSa. mirabilis . This result is in agreement with the sharing of morphological characters between these closely related species. Moreover, these two species are not as cavernicolous as literature previously indicated. They were caught in open rainforest in Gabon.